CONTROLLING IN HARDWARE PRODUCTION RUP «BMZ» - V. M. Machulin; V. E. Sidorchuk; S. N. Astratov; Yu. B. Kim; N. G. Lobanova (Литьë и металлургия, 2011)
The concept of control of financial and economical activity of hardware plant RUP «BMZ» is examined.